Government Scholarship Vietnam for International Students: Practices and Lessons Learned from Kemitraan Negara Berkembang (KNB) Scholarship Indonesia - Nguyen, Minh Tri (Journal of Education for Sustainability and Diversity, 2026)
This article explores the operations of the Government Scholarship Vietnam program and draws insights from the Kemitraan Negara Berkembang (KNB) Scholarship Indonesia. Both initiatives promote international cooperation and foster human resources development through academic exchanges. Through a comparative analysis of the structures, selection processes, and support mechanisms of these scholarships, this study highlights notable distinctions. It identifies effective strategies implemented by Indonesia that Vietnam could potentially adopt. The findings provide practical recommendations for Vietnam to enhance its scholarship program, thereby advancing its diplomatic, educational, and developmental objectives.